CLINICAL AND PATHOLOGICAL CHARACTERISTICS AND MOLECULAR SUBTYPES IN A PROSPECTIVE COHORT OF PATIENTS WITH BREAST CANCER ACCORDING TO ACCESS TO TREATMENT: SUPPLEMENTARY HEALTH CARE VERSUS UNIFIED HEALTH SYSTEM - Gomes Filho, José Euderaldo Costa; Rocha, Ariane Silva da; Fernandes, Gisele Aparecida; López, Rossana Verónica Mendoza; Curado, Maria Paula (Mastology, 2021)
The aim of this study was to describe the clinical and pathological characteristics and molecular subtypes in a prospective cohort of patients with breast cancer based on access to treatment — Supplementary Health Care versus Unified Health System (UHS). This is a cross-sectional study aligned to a prospective cohort developed at Hospital AC Camargo Cancer Center with 705 female patients, aged between 18 and 93 years and diagnosed with breast cancer. They had access to treatment by Supplementary Health (56.5%, n=398). Tumor topography for both UHS and Supplementary Health group include higher right breast, 53.4% (n=164) and 50.8 (n=202) (p=0.226); sublocation in the upper outer quadrant, 40.4% (n=124) and 52.3% (n=208) (p<0.001); T1 clinical staging, 37.8% (n=116) and 42.2% (n=168) (p<0.001); N0, 50.5% (n=155) and 54.3% (n=216) (p=0.109); and M0, 95.1% (n=292) and 93.5% (n=372) (p=0.667), respectively. For both UHS and Supplementary Health, pathological classification T1, 44.6 (n=137) and 46% (n=183) (p<0.001); the presence of regional lymph nodes and distant metastasis showing no difference in N0, 59.6% (n=183) and 54.8% (n=218) (p=0.451); M0, 93.8% (n=288) and 95% (n=378) (p=0.306); invasive ductal carcinoma, 81.4% (n=250) and 84.9% (n=338) (p<0.001); histological grade 2, 42.7% (n=131) and 44.5 (n=177) (p<0.001); nuclear grade 3, 60.3% (n=185) and 59.5% (n=237) (p=0.421); HER2 negative, 73.2% (n=216) and 79% (n=313) (p<0.001); estrogen positive, 80.4% (n=246) and 76.9% (n=306) (p=0.228); progesterone positive, 80.4% (n=246) and 76.9% (n=306) (p=0.280); Ki-67 positive, 99.6% (n=278) and 100% (n=393) (p<0.001); and molecular classification defined as Luminal B, 56.8% (n=167) and 50% (n=328), respectively. Access to treatment by UHS or Supplementary Health demonstrated significant difference in tumor sublocation, clinical and pathological T staging, morphology, histological grade, HER2, and Ki76, whereas there was no difference for clinical and pathological N and M staging, nuclear grade, estrogen, progesterone, and molecular classification.